Meta-analysis of miRNA expression profiles for prostate cancer recurrence following radical prostatectomy - Pashaei, Elnaz; Pashaei, Elham; Ahmady, Maryam; Ozen, Mustafa; Aydin, Nizamettin (PUBLIC LIBRARY SCIENCE, 2017)
Background Prostate cancer (PCa) is a leading reason of death in men and the most diagnosed malignancies in the western countries at the present time. After radical prostatectomy (RP), nearly 30% of men develop clinical recurrence with high serum prostate-specific antigen levels. An important challenge in PCa research is to identify effective predictors of tumor recurrence. The molecular alterations in microRNAs are associated with PCa initiation and progression. Several miRNA microarray studies have been conducted in recurrence PCa, but the results vary among different studies. Methods We conducted a meta-analysis of 6 available miRNA expression datasets to identify a panel of co-deregulated miRNA genes and overlapping biological processes. The meta-analysis was performed using the 'MetaDE' package, based on combined P-value approaches (adaptive weight and Fisher's methods), in R version 3.3.1. Results Meta-analysis of six miRNA datasets revealed miR-125A, miR-199A-3P, miR-28-5P, miR301B, miR-324-5P, miR-361-5P, miR-363*, miR-449A, miR-484, miR-498, miR-579, miR637, miR-720, miR-874 and miR-98 are commonly upregulated miRNA genes, while miR-1, miR-133A, miR-133B, miR-137, miR-221, miR-340, miR-370, miR-449B, miR-489, miR492, miR-496, miR-541, miR-572, miR-583, miR-606, miR-624, miR-636, miR-639, miR661, miR-760, miR-890, and miR-939 are commonly downregulated miRNA genes in recurrent PCa samples in comparison to non-recurrent PCa samples. The network-based analysis showed that some of these miRNAs have an established prognostic significance in other cancers and can be actively involved in tumor growth. Gene ontology enrichment revealed many target genes of co-deregulated miRNAs are involved in regulation of epithelial cell proliferation and tissue morphogenesis. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated that these miRNAs regulate cancer pathways. The PPI hub proteins analysis identified CTNNB1 as the most highly ranked hub protein. Besides, common pathway analysis showed that TCF3, MAX, MYC, CYP26A1, and SREBF1 significantly interact with those DE miRNA genes. The identified genes have been known as tumor suppressors and biomarkers which are closely related to several cancer types, such as colorectal cancer, breast cancer, PCa, gastric, and hepatocellular carcinomas. Additionally, it was shown that the combination of DE miRNAs can assist in the more specific detection of the PCa and prediction of biochemical recurrence (BCR). Conclusion We found that the identified miRNAs through meta-analysis are candidate predictive markers for recurrent PCa after radical prostatectomy.
Keywords: EPITHELIAL-MESENCHYMAL TRANSITION; CELL-PROLIFERATION; BIOCHEMICAL RECURRENCE; GROWTH; RISK; MYC; ADENOCARCINOMA; TUMORIGENESIS; SUPPRESSION; PROGRESSION; Science & Technology - Other Topics